Recovery of Body Awareness After Stroke: An Observational Study - Serrada, Ines; Hordacre, Brenton; Hillier, Susan (Frontiers in Neurology, 2021)
Background: Body awareness (BA) is a process that involves sensory awareness originating from the body’s physiological states, processes and actions, and is shaped by one’s attitudes, perceptions, beliefs and experience of social and cultural context. Impairments in body awareness after stroke are believed to be common and may be an important influence on recovery outcomes. However, recovery of body awareness is poorly understood and receives little consideration in rehabilitation. Aims: To investigate if body awareness changes over time following stroke; and identify if body awareness after stroke is associated with sensation, motor impairment, self-efficacy and quality of life. Methods: An exploratory longitudinal observational study was performed. Participants with a stroke diagnosis and associated motor impairment were recruited from an acute stroke unit. An assessment battery consisting of sensory and motor impairment and function, body awareness, self-efficacy and quality of life measures were used at baseline, one, three and six months. Results: A total of 105 people with stroke were recruited. Most recovery in sensation and body awareness occurred within the first month after stroke (all p<0.01). Sensation and body awareness were correlated with other clinical outcomes (motor impairment, self-efficacy and quality of life), demographics, and stroke specific clinical characteristics (all p<0.01). Conclusions: This is the first study to track recovery of body awareness after stroke and investigate the relationship it may have in recovery of sensation, motor impairment and function, self-efficacy and quality of life. Further research is now warranted to continue investigation of body awareness and to develop effective stroke-specific assessment and intervention strategies.